Use of herbal medicine related to anxiety and depression in the general population of southeast Iran during the COVID-19 pandemic - Hossein Yarmohammadi; Maryam Iranzadasl; Mohammad Mostafa Ansari Ramandi; Mohammad Gholami Fesharaki; Fereshteh Ghorat (Monaldi Archives for Chest Disease)
The COVID-19 pandemic has led to increased anxiety/depression and changes in people’s health behaviors. This study aimed to investigate health beliefs regarding using herbal medicine and its associated factors among Iranians. A cross-sectional study on the general population in Birjand (southeast Iran) was conducted using a survey questionnaire (an online platform for creating questionnaires, available at https://porsline.ir/) consisting of demographic characteristics and beliefs toward herbal medicine use, as well as a telehealth and hospital anxiety and depression scale questionnaire to address anxiety and depression disorders. All statistical analysis was done with SPSS software version 18, and a p-value of 0.05 or less was considered significant. The study included 619 participants with a mean age of 36.58±10.74 and a female rate of 61%. The overall use of herbal medicine was 385 (62%), 170 (28%) for prevention, 12 (2%) for treatment, 170 (28%) for relaxation, and 191 (31%) for other reasons. Using herbal medicine for relaxation (p=0.010) and prevention (p=0.02) was significantly associated with less anxiety, while using herbs for the treatment of COVID-19 had an association with no family history of Coronavirus infection (p<0.001). The majority of participants used herbal medicine for different purposes for COVID-19, and this health behavior had a relationship with anxiety/depression and family history of COVID-19. This study's findings would be useful to researchers and policymakers in improving health beliefs and behaviors during the other pandemic in Iran.